Mitigasi Risiko Pembiayaan KUR Syariah untuk UMKM : Studi Kasus di BSI KC Medan Ahmad Yani - Lubis, Meysa Chairani; Sugianto, Sugianto; M Nawawi, Zuhrinal (Universitas Hamzanwadi, 2025)
This study aims to examine the risk mitigation strategy for People's Business Credit (KUR) financing at BSI KC Ahmad Yani Medan through a descriptive qualitative approach. The analytical method used is the Miles and Huberman interactive model, which consists of data reduction, data presentation, and conclusion drawing. The results indicate that despite the implementation of the 5C principle, particularly regarding character aspects, financing risks still arise in the post-disbursement phase. Three main problems identified include: misuse of KUR funds for consumptive purposes, the absence or inaccuracy of business financial reports, and expansion failure due to weak customer managerial capacity. These findings confirm that character assessment alone is insufficient, necessitating a risk mitigation strategy that focuses not only on the initial phase but also includes ongoing interventions. These strategies include improving financial literacy and developing the human resources capacity of MSMEs, separating business and personal accounts, using more comprehensive and advanced technology, and implementing more proactive risk-based monitoring. Theoretically, these findings enrich the development of the risk mitigation model, moving from the classic 5C approach to a dynamic framework encompassing behavioral analysis, financial coaching, and adaptive monitoring, to create a more resilient, inclusive, and sustainable microfinance system